Endothelial HSPA12B regulates myocardial monocyte infiltration and inflammatory activity after myocardial infarction - Wang, Yana; Fan, Min; Chen, Linjian; Gill, Patrick Spencer; Wang, Xiaohui; Ha, Tuanzhu; Williams, David L.; Li, Chuanfu; Yang, Kun (Frontiers in Immunology, 2025)
IntroductionCardiac macrophages are essential mediators of inflammation and tissue remodeling following myocardial infarction (MI). Endothelial cell-specific heat shock protein A12B (eHSPA12B) has emerged as a key vascular regulator, but its role in modulating immune cell responses after MI remains unknown. This study investigates whether eHSPA12B regulates monocyte infiltration following MI injury.MethodsWe used endothelial cell-specific Hspa12b knockout (eHspa12b-/-) and wild-type (WT) mice to assess cardiac function and monocyte infiltration following MI. Cardiac resident macrophages and infiltrating monocytes were examined by flow cytometry 3 days post-MI. Plasma levels of pro-inflammatory cytokines were evaluated by ELISA following MI. To investigate the mechanism by which Hspa12b regulates immune response of macrophages, endothelial cells were transduced with adenovirus expressing HSPA12B followed by hypoxia challenge. In a separate experiment, endothelial cell-derived exosomes were prepared. Macrophages, Raw 264.7 or bone marrow derived macrophages (BMDMs) were incubated with endothelial cell conditioned medium or endothelial cell-derived exosomes. Macrophage phenotypes were examined by immunofluorescence staining, ELISA and qPCR. Protein degradation of toll-like receptor 4 (TLR4) and myeloid differentiation primary response 88 (MyD88) in macrophages was assessed by immunoprecipitation and Western blotting.ResultseHspa12b-/- mice exhibited significantly worsened cardiac function and increased infiltration of monocytes compared to WT controls at 3 days post-MI. Conditioned medium from HSPA12B-overexpressing endothelial cells promoted a pro-regenerative macrophage phenotype, characterized by reduced pro-inflammatory and increased anti-inflammatory cytokine production. HSPA12B was secreted via exosomes from endothelial cells, and these exosomes were sufficient to induce macrophage polarization. Mechanistically, uptake of HSPA12B-containing exosomes promotes the degradation of TLR4 and MyD88 in macrophages.DiscussionEndothelial HSPA12B plays a novel immunomodulatory role in controlling monocyte infiltration and immune activation following MI.